A renaissance of violence: homicide in early modern Italy - Rose, Colin (Cambridge University Press, 2019)
"Bartholomeo Minconi did not have the profitable day he hoped for in the market outside Medicina. The forty-year-old salt smuggler came to the large town directly east of Bologna, from his hometown of Lugo in the Romagna, in April of 1670. A notary from Bologna's criminal court, the Tribunale del Torrone, recorded his brother's testimony the next day, itself informed by the gossip of "many and diverse persons": Bartholomeo attempted to break up a fight between two of his fellow townsmen and smugglers, Francesco Zanconi and Baldissera Vetria. The pair argued over "a certain wagon of grain," which, presumably, was stuffed with their contraband. When harsh words left them "injured, both of them brought themselves forward with their guns in hand," and the men squared off to fight. Francesco pulled the trigger first, but his weapon jammed. Because all involved were neighbours, Bartholomeo Minconi tried to intervene in this brewing duel; he died in the ensuing crossfire. According to his brother, Bartholomeo was a peaceful citizen who had offered to settle the debt between Zanconi and Vetria out of his own funds.1 The smugglers' conflict, rooted in their illegal trade, arose from their familiarity with each other and might have been quelled by its virtues. That conflict came to violence in Medicina and occurred in the bright market day in a crowded square, where onlookers hid in doorways but still watched with fascination. A dispute over an unspecified debt between men, who otherwise cooperated in their illegal trade, left a third man, another smuggler, dead in the square, turning an argument into a homicide. Bartholomeo paid for his peacefulness with his life-one of sixty-one people in this North Italian province of some 225,000 to die violently in Bolognese lands in that late-century year"--